Mapping irrigation requirements of major crops in the coastal agro-climatic zone of Odisha using CROPWAT 8.0 and geospatial techniques - PATTANAIK, SHIVBRATA; JENA, PRACHI PRATYASHA; PAUL, JAGADISH CHANDRA; DAS, DWARIKA MOHAN (The Indian Journal of Agricultural Sciences, 2025)
The demand for water in agriculture sector is increasing due to the need for higher crop production to feed the growing population. The east and south-eastern coastal plain agro-climatic zone (ACZ) of Odisha is one of the fertile zones that demands sustainable water resource management in agriculture. A study was carried out during 2023 at College of Agricultural Engineering and Technology (Odisha University of Agriculture and Technology), Bhubaneswar, Odisha to determine the crop water requirement (CWR), irrigation requirement (IR) and irrigation scheduling of major crops grown in different districts of east and south-eastern coastal plain ACZ of Odisha using CROPWAT model and GIS software. Based on 10-years of the meteorological data from 7 districts (Kendrapara, Khordha, Jagatsinghpur, Puri, Nayagarh, Cuttack and part of Ganjam) and the soil condition of the coastal region, daily evapotranspiration was found to range from 3.73–4.86 mm/day and the effective rainfall ranged from 778.6–986 mm. The crop water requirement for kharif rice was the greatest at 850 mm, followed by maize at approximately 400 mm. During kharif, no irrigation was required for pearl millet or finger millet in this region. A map of crop water requirements and irrigation needs in the zone would be very useful for sustainable irrigation planning for different crops in seven different districts of the east and south-eastern coastal plain ACZ of Odisha. These findings offer valuable insights for optimizing water allocation in the agricultural sector which will contribute to more effective water resource management and agricultural planning in the region.